Geen ander naam - J. du Preez (Acta Theologica)
The increasing awareness that the church of Christ has to communicate its message of salvation in a religiously plural society, has contributed to the fact that in ecumenical circles the New Testament confessions about Christ as only Saviour of the world (e.g. in Acts 4:12) are being interpreted in a way that leaves room for other saviours as well. The author first of all presents his own interpretation of Acts 4:12. This is followed by a critical discussion of two recent re-interpretations of the text: Krister Stendahl's understanding of the text as love language and Gregory Baum's interpretation of it in socio-political terms. The author points out inter alia that Stendahl and Baum actually steer clear of the basic question as to whether texts like Acts 4:12 are meant to reveal to us that Christ is really the One and only Saviour for all people for all times, so that we ought to faithfully accept him as such. With regard to Christian people's attitude towards people of other faits, it is regarded as essential that the confession of Christ as the only true Saviour of the world should go hand in hand with true humility and tolerance born from love which God poured into our hearts through the Holy Spirit (Rm 5:5). The article concludes with a brief answer to the question about the destiny of those who have never  had the opportunity ot hear the Good News.